Development of Web-Based Science Teaching Materials in Dick and Carey Model School in SMP Al-Falah Surabaya - Jusa Indrawan; Mustaji; Harwanto (Institute of Computer Science (IOCS), 2022)
The purpose of this development is to produce a WEB-Based Science Teaching Material at SMP Al-Falah Surabaya. The development model used is Dick & Carey. The stages of development research on the Dick & Carey model consist of ten steps. The development process involves subject matter experts, instructional design experts and learning media experts to provide feedback and suggestions for improvement. In addition, the science subject teacher of SMP Al-Falah Surabaya as a user of WEB-Based Science Teaching Materials at this school also provided feedback and input. The use of WEB-Based Science Teaching Material Development Dick & Carey School Model for Science Subjects can effectively increase active learning interactions. The results of this development research are (1) School WEB-Based Science Teaching Materials are able to increase students' motivation in science lessons which were initially considered boring to be fun, and (2) Student responses and responses to WEB School-Based Science Teaching Materials are very good so that the material It is faster to understand and after validation from material experts, design experts and media experts, it is hoped that this school's WEB-Based Science Teaching Materials will be better.